2021
DOI: 10.3390/en14071834
|View full text |Cite
|
Sign up to set email alerts
|

Supplying Energy to Vulnerable Segments of the Population: Macro-Financial Risks and Public Welfare

Abstract: The purpose of the study is to assess the level of energy supply to the population of the Eastern Europe, Caucasus, and Central Asian (EECCA) countries, taking into account their financial risk and energy efficiency for households as potential socially vulnerable consumers. The research methodology is based on three approaches to determining the energy poverty of the population, as well as the integral index of energy supply to socially vulnerable segments of the population. Based on the results of the three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The energy development and utilization in Georgia are seriously unbalanced due to its relatively low energy resources, efficiency, and problems such as differences in economic development levels. With the development of globalization, the disparities in its local economic growth levels are further widened, hindering the development of energy resources, including renewable energy [50].…”
Section: Discussionmentioning
confidence: 99%
“…The energy development and utilization in Georgia are seriously unbalanced due to its relatively low energy resources, efficiency, and problems such as differences in economic development levels. With the development of globalization, the disparities in its local economic growth levels are further widened, hindering the development of energy resources, including renewable energy [50].…”
Section: Discussionmentioning
confidence: 99%
“…The study found out that there are four major factors influence the adoption of renewable energy technology in Poland. These include environmental concern, ease of use, financial incentives, and relative advantage [26,55,56].…”
Section: Conclusion Implications and Policy Recommendationsmentioning
confidence: 99%
“…Government is also supporting the implementation of renewable energy sources Ulewicz et al, 2021) and suggests to improve the usage of natural resources in an efficient manner (Haseeb et al, 2021;Deja et al, 2019). The effective implementation of renewable energy sources helps the countries considered as vulnerable segment who are living without proper energy supply (Smirnova, Szczepańska-Woszczyna, et al, 2021) as well as the country like Ukraine (Sabishchenko et al, 2020). Smart grid consists of smart meters, load control switches, distribution boards, renewable energy resources, energy storage, computers, etc.…”
Section: Introductionmentioning
confidence: 99%